Month of birth is associated with mortality among older people in Japan: Findings from the JAGES cohort. (20th April 2016) - Inoue, Yosuke; Stickley, Andrew; Yazawa, Aki; Fujiwara, Takeo; Kondo, Katsunori; Kondo, Naoki
ABSTRACT: Month of birth (MOB) has been linked to a variety of health conditions in adulthood. This study examined the association between MOB and mortality among the healthy elderly in Japan, where a practice of traditional age reckoning was employed up until the late 1940s. The results showed male participants born in December were more likely to die earlier while those born in January had lower mortality. It is possible that social factors in early life, such as the time period when a birth is officially registered, may have implications for health that stretch across the life course.